Pengaruh Media Google Drive Terhadap Motivasi Belajar Siswa Pada Pelajaran Akuntansi di UPT SMK Negeri 09 Ogan Komering Ilir - Lestari, Widya Indah; Aradea, Riswan; Januardi, Januardi (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The purpose of this study is to find out the Influence of Google Drive Storage Media on Student Learning Motivation in Accounting Lessons at UPT SMK Negeri 09 Ogan Komering Ilir. The population in this study is all students of class X Accounting at UPT SMK Negeri 09 Ogan Komering Ilir for the 2022/2023 Academic Year. Total sampling is a sampling technique when all members of the populations are used as samples. In this study, the researcher used a type of quantitative research with an experimental method. Data collections techniques are methods used in collecting information or information about research objects. The data analysis techniques use descriptive data analysis techniques. The results of this study indirectly show that Google Drive storage media can increase students’ motivation to learn, this is due to the interest and increased enjoyment of students learning using technology, research conducted by researcher also proves that the influence of Google Drive storage media on learning motivation is 36%. However, there are 64% that are influenced by other factors.